Underwater energy harvesting model for agricultural applications using stochastic network calculus - Vignesh, S. R.; Sukumaran, Rajeev (Institute of Advanced Engineering and Science, 2025)
Underwater wireless sensor network (UWSN) is a specialized type of wireless sensor network (WSN) designed for underwater communication among sensor nodes deployed in oceans for monitoring purposes such as observing marine life, detecting pollutants, and keeping track of oceanographic conditions. Managing limited energy in harsh underwater environments presents unique challenges compared to terrestrial networks. This research addresses this challenge by developing a reliable energy harvesting model. It analyzes the effects of delay and energy storage constraints on the energy harvesting rate (EHR), a measure of the energy replenished over time to maintain sensor node operations. It quantifies the amount of energy that can be harvested and stored within a given period, which is crucial for sustaining the network's functionality. The study includes analyzing and simulating the model analytically using discrete event simulators to evaluate delay performance bounds. Simulation results indicate that larger packet sizes require a higher minimum EHR, while stricter delay requirements decrease it for a fixed arrival rate.